2020
DOI: 10.1007/s10342-020-01328-x
|View full text |Cite
|
Sign up to set email alerts
|

Ninety-five years of observed disturbance-based tree mortality modeled with climate-sensitive accelerated failure time models

Abstract: Modeling disturbance-based tree mortality is becoming increasingly important in the discussion of how to adapt forests to climate change and to preserve their ecosystem services and mitigate the risk of economic losses. In this study, we fitted species-specific interval-censored Accelerated Failure Time models for five major tree species to derive the influence of climate, soil, silvicultural measures, stand and tree characteristics on survival times. We coded all disturbance-based mortality causes as events a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 80 publications
(106 reference statements)
2
14
0
Order By: Relevance
“…Precipitation increases were also associated with increased loss in some regions. This has been found in other studies (Maringer et al, 2021; Neumann et al, 2017) and although appearing counterintuitive can arise due to increased competition after forest growth spurts (Condit et al, 2004; McDowell, 2018) and the decoupling between precipitation and soil moisture which, in areas of groundwater depletion like NW India, is common (Condon & Maxwell, 2019; Zaveri et al, 2016).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…Precipitation increases were also associated with increased loss in some regions. This has been found in other studies (Maringer et al, 2021; Neumann et al, 2017) and although appearing counterintuitive can arise due to increased competition after forest growth spurts (Condit et al, 2004; McDowell, 2018) and the decoupling between precipitation and soil moisture which, in areas of groundwater depletion like NW India, is common (Condon & Maxwell, 2019; Zaveri et al, 2016).…”
Section: Discussionmentioning
confidence: 51%
“…Impacts of climate change on forests are often largely dependent on geographical location and interactions between climate variables (Allen et al, 2010; Brito‐Morales et al, 2018; Maracchi et al, 2005) but have been shown to both positively and negatively affect forest growth, mortality, productivity and distribution, alongside impacting the capability to deal with other stressors like drought and fire (IPCC, 2019; Ovenden et al, 2021). Temperature increases are by far the most commonly studied climate driver of forest mortality (Chen et al, 2011; Heikkinen et al, 2020; Maringer et al, 2021; Seidl et al, 2017) and have been shown to directly impact forest distribution and growth (Garcia et al, 2014; Lenoir & Svenning, 2015). Changes in precipitation have also been shown to affect forest survival, most commonly precipitation decreases (Aiba & Kitayama, 2002; Bennett et al, 2015; Chen et al, 2017; Phillips et al, 2009; Taccoen et al, 2019; Zhang et al, 2017), but the relationships are often complex (Bateman et al, 2016; Seidl et al, 2017) and can be highly dependent on forest type, previous conditions and phenotypical adaptations of species (Das et al, 2013; Greenwood et al, 2017; McDowell, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, trees are more threatened when temperature is high or water availability is low (Brandl et al 2020). An effect of the soil nutritional properties has also been demonstrated (Maringer et al 2021). Finally, air pollution due to nitrogen, sulphur deposition and ozone can also contribute to the weakening of forest ecosystems (Dietze and Moorcroft 2011).…”
Section: Introductionmentioning
confidence: 97%
“…It has been presented as the combination of interchangeable predisposing, inciting, and contributing factors (Sinclair (1965). Predisposing factors reduce tree ability to resist to a stress on the long term, inciting factors are usually caused by extreme events (Maringer et al 2021) and contributing factors are often insects or pathogens that cause the nal decline through hydraulic failure or carbon starvation (McDowell et al 2008). This model based on different causes that interact at different time and spatial scales was popularized by the decline spiral in the 1980's (Manion 1981).…”
Section: Introductionmentioning
confidence: 99%